4-Ethylguaiacol Modulates Neuroinflammation and Promotes Heme Oxygenase-1 Expression to Ameliorate Brain Injury in Ischemic Stroke - Weng, Wen-Tsan; Kuo, Ping-Chang; Scofield, Barbara A.; Paraiso, Hallel C.; Brown, Dennis A.; Yu, I-Chen; Yen, Jui-Hung (Frontiers in Immunology, 2022)
Ischemic stroke is caused by a sudden reduction in cerebral blood flow that subsequently induces a complex cascade of pathophysiological responses, leading to brain inflammation and irreversible infarction. 4-ethylguaiacol (4-EG) is reported to suppress inflammatory immune responses. However, whether 4-EG exerts anti-inflammatory effects in ischemic stroke remains unexplored. We evaluated the therapeutic potential of 4-EG, and examined the cellular and molecular mechanisms underlying the protective effects of 4-EG in ischemic stroke. The effect of 4-EG in ischemic stroke was determined by using transient middle cerebral artery occlusion (MCAO) animal model followed by exploring infarct size, neurological deficits, microglia activation, inflammation cytokine production, blood-brain barrier (BBB) disruption, and brain endothelial cell adhesion molecule expression, and microglial heme oxygenase-1 (HO-1) expression. Nrf2-/- and HO-1 inhibitor ZnPP-treated MCAO mice were also subjected to MCAO to evaluate the role of Nrf2/HO-1 pathway in 4-EG-mediated protection in ischemic stroke. We found 4-EG attenuated infarct size, neurological deficits, and BBB disruption in ischemic stroke. Further investigation revealed 4-EG suppressed microglial activation, peripheral inflammatory immune cell infiltration, and brain endothelial cell adhesion molecule upregulation in ischemic brain. Finally, we demonstrated the protective effect of 4-EG in ischemic stroke was abolished in Nrf2-/- and ZnPP-treated MCAO mice. Our results demonstrate 4-EG confers protection against ischemic stroke and reveal the protective effect of 4-EG in ischemic stroke is mediated through the induction of Nrf2/HO1 pathway. It suggests 4-EG could be developed as a novel therapeutic agent for ischemic stroke treatment.